TIKTOK VIDEOS AS LEARNING MEDIA TO IMPROVE STUDENTS' SPEAKING SKILLS - Ratna Rosanti, Ika; Tauhid, Tauhid (STIT Rakeyan Santang Karawang, 2024)
Nowadays, the use of social media and education are closely related. However, teachers and students still face new obstacles along with the changing situation. In a preliminary study, the researcher found that one of the problems is the lack of student engagement when using technology in speaking learning through online learning. Thus, the purpose of this study is to develop TikTok as an instructional video for SMPN 2 Penengahan to engage their speaking skills. The design of this study is a research and development design that applies the ADDIE work procedure (Analysis, Design, Development or Production, Implementation or delivery, and Evaluation). The participants of the study were an English teacher and 30 students of SMPN 2 Penengahan. Qualitative data were collected from pre-observation during online classes, semi-structured interviews, and observations. On the other hand, quantitative data were collected from questionnaires according to analysis needs, expert assessments, and observation sheets in the implementation phase using a Likert scale percentage. Material experts scored 55 out of 60/93.75%, with a very good category, Media experts scored 75 out of 80/91.66%, with a very good category. The score from the observation sheet results at the implementation stage was 89.58%, indicating that the media was in the very good category to be used as a learning aid to improve speaking skills. Thus, TikTok learning videos have been proven to improve students' speaking skills.